Pulse Wave Contour Analysis in Healthy Volunteers, and its Relation to Clinical Phenotyping in Unani Philosophy - Juveria Mahmood; Alokananda Chakraborty; Ghazala Javed; M.H. Kazmi (International Journal of Pharma and Bio Sciences, 2021)
Unani Medicine has an upsurge of interest especially in India, where it has been practiced as one of the Indian systems of medicine. In Unani System of Medicine predisposition to a disease as well as selection of a preventive and curative regime is primarily based on clinical assessment of a person which includes one’s body constitution termed “Mizaj”. Mizaj / Temperament are a consequence of relative proportion of four entitles dam (blood), Balgham (Phlegm), Safra (Bile) and Sauda (melanin). The body is a united confluence of four humours and the temperaments acts as a force in health and disease. Human temperament is commonly denoted by dominant humour, it emulates a journey from an atom, molecule, cell, tissue, organ to human body. The health can be preserved and maintained as long as humours are in homeostasis with the overall physiology of the body. The individual humoural balance is also influenced by lifestyle factors. The Unani philosophy has 4 humours which under clinical phenotyping is designated as Sanguine, (Damvi) Phlegmatic (Balghami), Bilious (Safravi) and Melancholic (Saudavi). The analysis of Pulse and its ten forms in unani system plays a great role in Unani philosophy and hence it was of our interest to study and analyze the pulse wave and its forms. It validates some of the Unani concepts of humours or temperament with pulse wave contour analysis. A specially designed case record form as per the Unani classical text was designed for assessment of humours and the information obtained were recorded from healthy volunteers as subjects and determination of pulse wave analysis was performed by 16-Channel Biopac System. The temperaments of the present study showed that Pulse Wave analysis in healthy volunteers though all are in physiological range but found highly significant in safravi subjects when compared to balghami followed by damavi and saudavi.